The differential diagnosis and treatment of normal-pressure hydrocephalus - Kiefer, Michael; Unterberg, Andreas (Deutsches Ärzteblatt, 2012)
Normal-pressure hydrocephalus (NPH) was the first treatable type of dementia ever described and attracted much interest as soon as it became known. S. Hakim described the entity he called normal-pressure hydrocephalus in 1963 (e1, e2). In the ensuing...